Proposed system for analyzing the location of preschools: a Brazilian case study - Endler, Kellen Dayelle; Scarpin, Cassius Tadeu; Arns Steiner, Maria Teresinha (Brazilian Journal of Operations & Production Management, 2017)
Early infant education and care have become priority issues in Brazil. The present article evaluates the spatial distribution of public preschools in the municipality of Curitiba, in Paraná State, Brazil. This problem is an important aspect of school administration and can relieve problems of inequality in public education, such as accessibility and availability of places. The main contribution of this article is the system it proposes for rationalizing decision-making in the education system in question. This system presents four complementary analyses, although they are independent of one another: (i) analysis of the current location of facilities; (ii) analysis of the proposed location; (iii) analysis for expanding the capacity of existing units; and (iv) analysis of the opening of new facilities. The models were generated using VB.NET© modeling language and were solved by the CPLEX© solver. The results showed that, in general, there is a need for immediate planning to increase the number of places available in public infant education in Curitiba, which is also a requirement for compliance with the goals of the National Education Plan (NEP) that is now in force nationwide.